Arctic shipping risk management: A bibliometric analysis and a systematic review of risk influencing factors of navigational accidents. (July 2021) - Fu, Shanshan; Goerlandt, Floris; Xi, Yongtao
Highlights: Bibliographic analysis of literature on Arctic shipping risk management is presented. Patterns in year and journal of publication, keywords, and country of origin are analyzed. Systematic review of articles presenting quantitative risk analyses of navigational accidents is made. Risk Influencing Factors are extracted and synthesized in a qualitative model. Abstract: With the diminishing extents of Arctic sea ice, Arctic shipping becomes increasingly attractive for the shipping industry. Voyages along Arctic sea routes have seen a significant increase in recent years. Given the harsh environment, shipping operations in the Arctic constitute a hazardous activity for people onboard vessels, while vessels pose risks to vulnerable ecosystems and traditional socio-cultural environments. Given this emerging trend, this paper presents a bibliometric analysis of the broad academic literature related to risk management of Arctic shipping, published in the period from 2000 to 2019. Based on 221 articles, the bibliometric analyses provide insights in publication patterns concerning the year of publication, keywords, journals, and countries/regions from which the work originates. Furthermore, through a qualitative systematic review, this article presents a synthesis of risk influencing factors (RIFs) of navigational accidents in the Arctic, based on published quantitative risk models containing accident scenarios in Arctic shipping. To this effect, ten papers are investigated in detail, focusing on the scenario, methods, data sources, and RIFs. Identifying major thematic clusters in the RIFs, a model is proposed for synthesizing and illustrating the relationships among environmental and ship-related RIFs, and accident scenarios in Arctic shipping. A discussion is made concerning challenges in the research domain and future research directions, focusing on the strength of evidence in the risk models, the use of linear versus complex, systemic accident theories, and on the alignment of academic work with focus issues in regulatory contexts.